Politeness And Respect: The Strategy Of Communicating Winisatawan In Bali Province Tourism Village - Ngurah Byomantara, Dewa Gde (Devotion : Journal of Research and Community Service, 2024)
Research on civility and respect is an important theme in a pragmatic context. The existence of norms of politeness and respect based on ethical aspects serves as a guideline in behaving in a socio-cultural group environment in order to obey all existing rules, and behave so as not to cause gaps. Having respect for others will maintain our polite attitude in establishing relationships or interactions with others so as to create harmony and peace in social life. This type of research refers to quantitative research. The subjects of the study included tour guides, taxi drivers, pondok wisata waiters, restaurant waiters, food vendors, souvenir sellers, pecalang, and the community as independent variables. While domestic and foreign tourists as variables are bound. Data were collected using reflective questionnaires. All three instruments were expertly validated before being used to obtain readability, reliability, and validity Data was statistically analyzed using Two-Path Variance Analysis with linear multiple regression analysis techniques. The results showed that tour guides, pondok wisata staff, taxi drivers, restaurant waiters, food and beverage sellers, souvenir sellers, pecalang, and the public felt that they could communicate with domestic and foreign tourists with politeness and respect with great courtesy and respect to less politeness and less respect. And, the politeness of acting representative, assertive, directive, declarative, and expressive speech has a significant effect on the satisfaction of domestic and foreign tourists. There are 40 samples collected in this research.